The final kingdom - Northrop, Michael (Northrop, Michael. TombQuest, 2016)
As The Order's undying army of stone warriors, summoned by ancient Egyptian spells, draws near the border of the world and threatens to invade, Alex and Ren have to find a way to stop mummies and evil spirits from devastating the globe, even if they have to travel to the land of the dead to do it.